Judgments at Gaze Value: Gaze Cuing in Banner Advertisements, Its Effect on Attention Allocation and Product Judgments - Palcu, Johanna; Sudkamp, Jennifer; Florack, Arnd (Frontiers in Psychology, 2017)
Banner advertising is a popular means of promoting products and brands online. Although banner advertisements are often designed to be particularly attention grabbing, they frequently go unnoticed. Applying an eye-tracking procedure, the present research aimed to a) determine whether presenting human faces (static or animated) in banner advertisements is an adequate tool for capturing consumers’ attention and thus overcoming the frequently observed phenomenon of banner blindness, b) to examine whether the gaze of a featured face possesses the ability to direct consumers’ attention toward specific elements (i.e., the product) in an advertisement, and c) to establish whether the gaze direction of an advertised face influences consumers subsequent evaluation of the advertised product. We recorded participants’ eye gaze while they viewed a fictional online shopping page displaying banner advertisements that featured either no human face or a human face that was either static or animated and involved different gaze directions (toward or away from the advertised product). Moreover, we asked participants to subsequently evaluate a set of products, one of which was the product previously featured in the banner advertisement. Results showed that, when advertisements included a human face, participants’ attention was more attracted by and they looked longer at animated compared with static banner advertisements. Moreover, when a face gazed toward the product region, participants’ likelihood of looking at the advertised product increased regardless of whether the face was animated or not. Most important, gaze direction influenced subsequent product evaluations; that is, consumers indicated a higher intention to buy a product when it was previously presented in a banner advertisement that featured a face that gazed toward the product. The results suggest that while animation in banner advertising constitutes a salient feature that captures consumers’ visual attention, gaze cuing can be an effective tool for driving viewers’ attention toward specific elements in the advertisement and even shaping consumers’ intentions to purchase the advertised product.